PWE-040 Comfort Scoring For Endoscopic Procedures: Who Is Right – The Endoscopist, The Nurse Or The Patient?. (9th June 2014) - Rafferty, H; Hutchinson, J; Ansari, S; Smith, L-A
Abstract : Introduction: Patient experience is a key aspect of endoscopy service quality. It is a Global Rating Scale (GRS) requirement to capture data on patient comfort. In our unit comfort scores are recorded by the endoscopist and by the endoscopy nurse using the Modified Gloucester Scale (1=no discomfort to 5=severe discomfort). Patients do not usually record a score. We suspected there may be differences in comfort assessment between these different groups, which may affect the value of this quality indicator. Methods: Comfort data was prospectively collected from patients undergoing an endoscopic procedure (either an esophagogastroduodenoscopy (OGD), colonoscopy or flexible sigmoidoscopy (FS)), over a three week period (April–May 2013). Endoscopist and nurse recorded scores were collected for each procedure from the endoscopy documentation, and a patient comfort score was completed by the patient in the recovery area. The endoscopists and nurses were unaware that the comfort data was going to be studied. The wilcoxon matched pairs signal rank statistical test was used to look for comfort score differences between the groups. Results: A total of 139 procedures were included in the analysis. The OGD mean comfort scores were: endoscopist 1.3 (SEM, 0.1), nurse 1.6 (SEM, 0.1), patient 1.4 (SEM, 0.1). A significant difference was found between the endoscopist and nurse comfort scores (p < 0.01). No significant difference was found for FS comfort scores: endoscopist 1.8 (SEM, 0.1), nurse 1.6 (SEM, 0.1), and patient 1.8 (SEM, 0.2). For colonoscopy, the mean scores were: endoscopist 1.7 (SEM, 0.1), nurse 2.1 (SEM, 0.2), patient 1.6 (SEM, 0.2). A significant difference was found between patient and nurse comfort scores (p < 0.01), but not between the patient and endoscopist comfort scores. Conclusion: Endoscopy nurses gave a higher comfort score (more discomfort) than patients and endoscopists for OGD and colonoscopy, with no difference between the groups for FS comfort scores. These results suggest that the perception of procedure related discomfort differs between these three groups, particularly between endoscopists and nurses. As patient experience is a key aspect of endoscopy service quality, it is important to recognise that there are differences between the perceived comforts levels between the endoscopist, the nurse and the patient. Disclosure of Interest: None Declared.